Cooperação em jogo no jornalismo? : uma análise da interação fonte off e jornalista - Marlow, Rosani Muniz (2016)
Pragmatics of language proposes theoretical perspectives that are empirically based attempts to describe the sociolinguistic cognitive processing. This work proposes to study the interactions between journalist and off sourcewith purposes to produce news for printed newspaper. The interest is through estrangement that anonymous sources of information is conveyed in the papers, preliminarily setting a cooperation in game: from the off source, by not to allowing the disclosure of their identity, thus absolving themselves of responsibility and consequences, which falls on the reporter and / or the communication company; and from the journalist in relation to the printed newspaper reader, because when one publishes anonymous source content, the journalist legitimates information of secret authorship , which makes questionable the values credited to journalism, such as ethics, fairness and truthfulness. The research seeks to understand the aspects of journalistic and political spheres that contribute to the understanding of the interaction which is object of analysis, and consider the theories of the Cooperation Principle, Paul Grice ([1975]; 1982; 1996), and the Relevance Principle, Dan Sperber and Deirdre Wilson (1995; 2005), applying them to 162 instances of off in political news of the newspaper A Tribuna, from the State of Espírito Santo, referring to the election campaing of the years 2012 and 2014. As a result, the off does not set a break of the principle of cooperation between the interactants nor those relative to the printed newspaper reader, since the apparent rupture is a speaker's resource to insert content beyond the linguistic sentence, in an expectation that the other party will make cognitive inferences necessary for the understanding and maintenance of interaction, configuring cooperation. The relevance of the off information, in turn, is sought and built cognitively by the reader, considering social and political contexts as well as interests of everyone involved: off source, journalist/communication company and consumer/reader.